Exploration of a Stirling engine and generator combination for air and helium media. (5th March 2019) - Shufat, Salem Alarabi; Kurt, Erol; Cinar, Can; Aksoy, Fatih; Hançerlioğulları, Aybaba; Solmaz, Hamit
Highlights: A new concept namely, power generation capability per pressure is proposed. The coupling of a Stirling engine and an axial flux generator has been explored. The characteristic of the coupled system has been identified for air and helium. The power increase per pressure has been found as 830 W/bar for helium. The electrical power obtained from the system reaches up to 270 W for helium. Abstract: In the present paper, a hybrid machine, which converts the heat energy to directly electricity has been implemented. The new machine uses a beta-type Stirling engine and a generator coupled to the rotating flywheel unit of the engine. The system has been operated under various charge pressures of Helium and air using a liquefied petroleum gas heater. It has been measured that the direct coupled system can produce electricity efficiently. The generated voltage amplitude increases linearly by the speed of engine. The waveform type is also ideal sinusoidal although the machine rotates at low speeds, that makes the machine valuable in terms of electricity conversion. The pressure of the gas affects the operation of the engine, substantially in the sense that higher pressure rates yield to higher speeds and that enables to generate high powers if an optimal electrical load is used at the output of the three phase electrical generator. It is proven that the electrical power of 270 W is generated at 744 rpm under the pressure of 0.85 bar for Helium filled engine.